Repeatability and predictive value of lactate threshold concepts in endurance sports - Heuberger, J. A. A. C.; Gal, P.; Stuurman, F. E.; de Muinck Keizer, W. A. S.; Mejia Miranda, Y.; Cohen, A. F. (PLOS ONE, 2018)
Blood lactate concentration rises exponentially during graded exercise when muscles produce more lactate than the body can remove, and the blood lactate-related thresholds are parameters based on this curve used to evaluate performance level and help athletes optimize training. Many different concepts of describing such a threshold have been published. This study aims to compare concepts for their repeatability and predictive properties of endurance performance. Methods: Forty-eight well-trained male cyclists aged 18-50 performed 5 maximal graded exercise tests each separated by two weeks. Blood lactate-related thresholds were calculated using eight different representative concepts. Repeatability of each concept was assessed using Cronbach`s alpha and intra-subject CV and predictive value with 45 minute time trial tests and a road race to the top of Mont Ventoux was evaluated using Pearson correlations. Results: Repeatability of all concepts was good to excellent (Cronbach`s alpha of 0.89-0.96), intra-subject CVs were low with 3.4-8.1%. Predictive value for performance in the time trial tests and road race showed significant correlations ranging from 0.65-0.94 and 0.53-0.76, respectively. Conclusion: All evaluated concepts performed adequate, but there were differences between concepts. One concept had both the highest repeatability and the highest predictability of cycling performance, and is therefore recommended to be used: the Dmax modified method. As an easier to apply alternative, the lactate threshold with a fixed value of 4 mmol/L could be used as it performed almost as well.